OVERVIEW OF THE BEARING CAPACITY FINNED CONCRETE SLABS BASED ON SLOPE OF THE FINS USING NUMERICAL METHOD - Mandagi, Nashril Ananta; Yusuf, Muhammad; Bachtiar, Vivi (Fakultas Teknik Universitas Tanjungpura, 2023)
Indonesia is a country that has a land area of approximately 1.905 million km ². Facilities and infrastructure are needed to support community mobility to balance the land area. One of the infrastructures needed to carry out this mobilization is roads. In building roads, it is necessary to pay attention to safety and comfort aspects so the community can optimally use these facilities. Experts have contributed much of their thoughts to create a road construction used today. Concrete Structure is a common structure used by experts for road construction in Indonesia. Concrete construction was chosen because it is easy to form and stiff so it is easy to adapt to regions in Indonesia. However, road damage still occurs frequently, so a more effective construction system is needed to reduce road damage. In the previous study (Sirait et al., 2022; Syenna et al., 2022), experimental research was carried out in the form of finned concrete slab construction which functions to increase the bearing capacity of the concrete slab. Variations on the tilt of the fins are used, namely 0 °, 10 °, 20 °, 30 °, and 40 °. This study found that concrete slabs with a fin slope of 30 ° produced the greatest carrying capacity of the other sample models. This research is still reviewing the same aspect, namely finding the optimal fin slope on concrete slab samples with variations of fin slope of 0 °, 10 °, 20 °, 30 °, and 40 °. However, the method used is a numerical method by making approximations to the original conditions of the samples. Simulating loading tests on cohesive soils and non-cohesive soils carried out samples. By this numerical method, it was found that concrete slabs with a fin slope of 10 ° had the highest bearing capacity of the other samples.